2014
DOI: 10.4172/2155-6113.1000321
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Malaria in HIV-Infected Pregnant Women on Anti-Retroviral Therapy in Enugu, South East Nigeria

Abstract: There are high rates of maternal morbidity including fever, severe anaemia, abortion, still birth, and placental malaria among these women.Consequently, babies can be born with low birth weight due to both prematurity and intrauterine growth retardation [3,10]. However, epidemiological studies of the prevalence and clinical manifestations of P. Falciparum malaria in HIV-infected pregnant women that consider factors such as residential location, CD4 level, viral load, and adherence to intermittent preventive tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
6
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 16 publications
4
6
3
Order By: Relevance
“…Furthermore, the CD 4 + T cell count was significantly lower in HIV patients coinfected with malaria compared to those without, which confirms the study by Tay et al [14] in which patients with malaria were also observed to have lower CD 4 + T cell count. The finding of a significant association between malaria prevalence and CD 4 + T cell count is contrary to studies performed elsewhere [23, 25]. …”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the CD 4 + T cell count was significantly lower in HIV patients coinfected with malaria compared to those without, which confirms the study by Tay et al [14] in which patients with malaria were also observed to have lower CD 4 + T cell count. The finding of a significant association between malaria prevalence and CD 4 + T cell count is contrary to studies performed elsewhere [23, 25]. …”
Section: Discussioncontrasting
confidence: 99%
“…Malaria in Yaounde can be described as holoendemic and seasonal [18]. The prevalence is also very low compared to the prevalence of malaria in the other high risk groups including children (where prevalence could be as high as 98 % in some settings) [24], and pregnant women [25]. The low prevalence of malaria in this group could be attributed to the health seeking attitude of HIV patients.…”
Section: Discussionmentioning
confidence: 99%
“…Interventions with IPTp-SP3 and CTX for pregnant women with HIV were highly cost-effective, constituting important evidence considering the negative feedback of PAM-HIV coinfection, whose intervention would reduce the negative effects of both. HIV potentiates the consequences of PAM by increasing the parasitic density, anaemia, cerebral and placental malaria, preterm delivery, LBW and neonatal death; PAM, in turn, increases viraemia, the progression to AIDS and the risk of vertical transmission of HIV [ 4 , 62 , 63 , 64 ]. However, the cost-effectiveness of this intervention depends, to a large extent, on close adherence to the daily dose (>80%) [ 43 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Malaria, a mosquito-borne parasitic infection caused by species of Plasmodium, is the leading cause of pregnancyassociated death in sub-Saharan Africa (Sanyaolu et al, 2013;Sonny-Johnbull et al, 2014;Gething et al, 2016;Maitland, 2016;Sued et al, 2016). In sub-Saharan Africa, 25 million pregnant women are currently at risk for malaria, accounting for 10,000 maternal and 200,000 neonatal deaths per year (Matangila et al, 2014;Mbah et al, 2015).…”
Section: Introductionmentioning
confidence: 99%